Pengaruh Kegiatan Eksperimen Mengenal Hujan Terhadap Kemampuan Sains Anak Usia Dini - Heri Hidayat; Fadhilla Ayuningtyas; Eva Aulia Nur; Ina Siti Halimatuss; Dinda Putri Fatimah (IJIGAEd: Indonesian Journal of Islamic Golden Age Education, 2026)
This study aims to analyze the effectiveness of a natural phenomenon-based experimental method, specifically the Rain Recognition activity, in improving early childhood science process skills. The main issue addressed is the need for an instructional approach capable of transforming abstract science concepts into concrete, meaningful experiences for children. Utilizing a quantitative descriptive method, this research was conducted at RA Al Hasanah. Data were collected through observations and tests, then analyzed statistically. The results indicate an improvement in the average score of children's science abilities after the experimental activities, from 22.14 to 22.79. These findings demonstrate that active engagement in experimentation, observation, and problem-solving is highly effective in building cognitive understanding and critical thinking skills. In conclusion, context-based experimental learning contributes positively to the development of early science literacy. The implications of this study emphasize the importance for educators to implement direct exploration methods, providing children with opportunities to understand natural phenomena through hands-on experience